Comparison of TSH Levels Pulmonary Tuberculosis Patients at The Phase 0 and 6 Months Treatment - Qo'imah, Alamanda Nurul; Wardani, Dita Pratiwi Kusuma; Sudarsono, Tantri Analisawati; Mulyanto, Arif (jitek, 2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Pulmonary TB has become a health problem worldwide, including in Indonesia, because the sufferers' prevalence is increasing every year. The increase in TB drug resistance will pose a severe health threat. The continuous consumption of drugs in large quantities and high doses can affect the function of the thyroid gland. This study aimed to determine the levels of thyroid stimulating hormone (TSH) in pulmonary tuberculosis patients with treatment phases of 0 months and six months. This research is analytical observational research with a cross-sectional research design. The sampling method uses accidental sampling. A total of 42 respondents participated in this study to determine the levels of TSH in pulmonary TB. The results of the Mann-Whitney U test showed no difference in TSH levels in pulmonary TB patients with different treatment phases of 0 months and six months (p = 0.3). There was no significant difference between TSH levels in pulmonary TB patients in the 0 and 6-month treatment phases.